Prenylflavonoids from Flourensia fiebrigii - Uriburu Monasterio, Maria Laura (2007)
Three compounds: (2S)-8-(3″-methylbut-2″-enyl)-7,3′,4′-trihydroxyflavanone, (2S)-8-(3″-methyl-4″-hydroxy-but-2″-enyl)-7,3′,4′-trihydroxyflavanone and (2S)-8-(3″-methyl-4″-hydroxy-but-2″-enyl)-5,3′,4′-trihydroxy-7-methoxyflavanone, along with five previously known compounds, were isolated from the aerial parts of Flourensia fiebrigii. Their structures were elucidated by application of various spectroscopic methods, including 1D and 2D NMR techniques. © 2007 Elsevier Ltd. All rights reserved.